EFFECT OF DIFFERENT FERTILIZER SCHEMES AND IRRIGATION INTERVALS ON TOMATOES’ RESPONSE TO WATER SHORTAGE - Pascual, Pet Roey R.; Cabahug, J P. (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 17 No. 1, 2014, 2018)
The growing concerns on increasing global water scarcity require efficient use of water resources.   Aimed to investigate the growth and yield responses of tomato to water stress in varied fertilization scheme, a two-factor experiment involving three (3) fertilizer management practices (use of recommended inorganic fertilizer, organic fertilization at 10 T/ha and 20 T/ha) and three (3) watering schedules (daily, two days interval, and three days interval) was done. Analysis of the plant height showed that at increased level of organic fertilizer, plants were taller even up to three (3) days watering interval. Height was significantly reduced for plants applied with  10  T/ha  compost  and  watered  at  three  (3)  days  interval  and  those  applied  with  pure inorganic  fertilizer.    Moreover,  prolonging  the  interval  of  watering  up  to  three  (3)  days  on compost-fertilized tomatoes allowed them to initiate flowering earlier.  This was not significantly different with tomatoes applied with pure inorganic fertilizer but watered daily.   Finally, examination of the analysis on the cumulative yield showed that the highest yields, 10.54 and 8.96 MT/ha, were obtained on tomatoes applied with 20 T/ha compost and watered daily and at two (2) days interval, respectively.   Significant reduction  in  yield  was exhibited  by tomatoes applied with inorganic fertilizer only and watered daily, more so, when watering was at two (2) and three (3) days interval.   A conclusion  is drawn  that application of compost reduces the negative effects of water shortage to flower initiation and plant height even up to three (3) days watering interval and up to two (2) days interval to yield.